Prevalence of Parathyroid Carcinoma and Atypical Parathyroid Neoplasms in 153 Patients With Multiple Endocrine Neoplasia Type 1: Case Series and Literature Review - Song, An; Yang, Yi; Liu, Shuzhong; Nie, Min; Jiang, Yan; Li, Mei; Xia, Weibo; Wang, Ou; Xing, Xiaoping (Frontiers in Endocrinology, 2020)
Purpose: The occurrence of parathyroid carcinoma (PC) and atypical parathyroid neoplasm (APN) in multiple endocrine neoplasia type 1 (MEN1) is rare. The present paper reports the cases of 3 MEN1-PC/APN patients at our center and discusses the prevalence in a Chinese MEN1 cohort. Methods: This report is a retrospective analysis of 153 MEN1-associated primary hyperparathyroidism (MEN1-HPT) patients at our center, which included 3 MEN1-associated PC/APN (MEN1-PC/APN) patients. The clinical manifestations, biochemical indices, pathological findings, and therapy have been summarized along with the report of the genetic testing of the 3 patients. Results: Of the 153 MEN1-HPT patients, 1 (0.7%) was histopathologically diagnosed with PC and 2 (1.3%) with APN. Three heterozygous mutations were identified in the 3 MEN1-PC/APN patients (c.917 T > G, c.431T > C, and c.549 G > C). The cumulative findings of 3 cases with 18 previously reported MEN1-PC/APN cases revealed that the mean serum calcium (Ca) level was 3.15 ± 0.44 mmol/L and the median parathyroid hormone (PTH) level was 327 pg/mL (214.1, 673.1), both of which were significantly higher as compared to the respective levels in non-PC/APN MEN1 patients at our center (Ca: 2.78 mmol/L [2.61, 2.88], PTH: 185.5 pg/mL [108.3, 297.0]; P = 0.0003, 0.0034, respectively). Conclusion: MEN 1-PC/APN is a rare disease, with a prevalence of only 2.0% among the MEN1-HPT cohort at our center. The affected patients recorded higher serum Ca level and PTH levels than those with MEN1-associated benign tumors. However, the diagnosis of MEN1-PC/APN is based upon pathology most of the times. Key words: multiple endocrine neoplasia type 1, parathyroid carcinoma, atypical parathyroid neoplasms, prevalence, Chinese population